Prediction of Load in Reverse Extrusion Process of Hollow Parts using Modern Artificial Intelligence Approaches - M. Shariat Panahi; N. Moshtaghi Yazdani (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Extrusion is one of the important processes to manufacture and produce military and industrial components. Designing its tools is usually associated with trial and error and needs great expertise and adequate experience. Reverse extrusion process is known as one of the common processes for production of hollow parts with closed ends. The significant load required in formation of a workpiece is one of the existing constraints for the reverse extrusion process. This issue becomes rather difficult especially for the parts having thin walls since its analysis using finite element softwares is exposed to some limitations. In this regard, application of artificial intelligence for prediction of load in the reverse extrusion process will not only save time and money, but also improve quality features of the product. Based on the existing data and methods suggested for variations of punching force through the reverse extrusion process, the system is trained and then performance of the system is evaluated using the test data in this paper. Efficiency of the proposed method is also assessed via comparison with the results of others.DOI:http://dx.doi.org/10.11591/ijece.v4i3.5356